Echocardiographic-derived Pulmonary Artery Pulsatility Index: towards non-invasive evaluation of right ventricular function. (4th February 2022) - Boretto, P; Gravinese, C; Frea, S; Pidello, S; De Ferrari, GM
Abstract: Funding Acknowledgements: Type of funding sources: None. Background. Pulmonary artery pulsatility index (PAPi)(1) is a powerful predictor of right ventricular failure in patients with acute inferior myocardial infarction(2) and in patients with heart failure undergoing LVAD implantation(3). PAPi derivation requires invasive right heart catheterism (RHC), thus limiting availability and seriate assessment of right ventricular function. Purpose. Aim of the study was to evaluate accuracy and agreement of echocardiographic derived PAPi (ePAPi) compared to right heart catheterism derived PAPi in heart failure with reduced ejection fraction (HFrEF) patients. Methods. ePAPi was defined as the ratio of pulmonary artery pulse pressure (sPAP – dPAP) to right atrial pressure (RAP). Systolic pulmonary artery pressure (sPAP) was determined from tricuspid regurgitation (TR) velocity using the simplified Bernoulli equation(4): sPAP = 4 x (peak TR jet velocity)2 + RA pressure. Diastolic pulmonary artery pressure (dPAP) was calculated as: dPAP = 4 x (end-diastolic pulmonary regurgitant velocity)2 + RA pressure. Simplified ePAPi, defined as peak TR pressure to RA pressure ratio was also investigated. Pearson and Spearman correlation tests were performed. A Bland-Altman plot analysis was performed to assess agreement between ePAPi and invasive PAPi. ROC curves were made to assess ePAPi accuracy in identifying patients with low PAPi (defined as PAPi < 2 and PAPi < 3.65). Results. 66 HFrEF patients (age 59 ± 10 years, 63% males, mean EF: 35 ± 9%) underwent RHC and blinded echocardiogram in a single center Cardiology Departement. Mean invasive derived PAPi was 4.4 ± 3.6, while ePAPi was 3.9 ± 2.3. ePAPi showed an excellent correlation with invasive PAPi (Pearson r: 0.80, p < 0.001; Spearman rho: 0.83, p < 0.001) and good agreement as shown in Bland Altman plot (figure 1). In ROC analysis, ePAPi accurately identified patients with low hemodynamic PAPi < 2 (Sensibility: 100%; Specificity: 87.2%; AUC: 0.97; Youden criterion: ePAPi < 2.3) and PAPi < 3.65 (Sensibility: 81.8%; Specificity: 84%; AUC: 0.89; Youden criterion: ePAPi < 3.6)(figure 2). Simplified ePAPi also showed good correlation and agreement (Pearson r: 0.58, p < 0.001; Spearman rho: 0.81, p < 0.001). Conclusions. In patients with HFrEF, echocardiographic derived PAPi showed a good agreement and correlation with invasive derived PAPi. ePAPi was also accurate in identifying patients with low PAPi values associated with poor outcomes and may be of interest for non-invasive right ventricular function seriate assessment. Further studies are needed to investigate prognostic implications.